2018
DOI: 10.1080/14686996.2018.1487761
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles reduce the apoptosis induced by tumor necrosis factor-α

Abstract: Silver nanoparticles (AgNPs) are widely known to have anti-inflammatory properties, but the exact mechanism underlying this anti-inflammatory effect is not clearly understood. Tumor necrosis factor-α (TNFα) is a major pro-inflammatory cytokine that is expressed in the early stage of cell inflammation and induces apoptosis by several known pathways. Our study aimed to investigate the effect of AgNPs on the response of lung epithelial cells to TNFα and the molecular mechanism of this response. Lung epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
(21 reference statements)
0
17
1
Order By: Relevance
“…In our previous study on AgNPs synthesized using Pimpinella anisum seeds, we also found that 12 μg of AgNPs was toxic to HCT116 cells by enhancing either apoptosis or necrosis [ 12 ]. A low concentration of AgNPs was also reported to be able to induce apoptosis [ 39 ]. The current experiments with AgNPs synthesized with Punica granatum peel extract also showed 55–62% toxicity with 12.5 μg.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study on AgNPs synthesized using Pimpinella anisum seeds, we also found that 12 μg of AgNPs was toxic to HCT116 cells by enhancing either apoptosis or necrosis [ 12 ]. A low concentration of AgNPs was also reported to be able to induce apoptosis [ 39 ]. The current experiments with AgNPs synthesized with Punica granatum peel extract also showed 55–62% toxicity with 12.5 μg.…”
Section: Resultsmentioning
confidence: 99%
“…Potential toxicity of nanoparticles and their effect on growth, development and health were investigated in studies conducted on leukemic cell lines [ 87 ], the chicken embryo model and broiler chickens [ 34 , 35 ]. In vitro studies showed a toxic effect of AgNPs on keratinocyte cells, triggering apoptosis, while a higher percentage of necrotic monocytes was observed [ 88 ]. The use of silver, gold, copper and palladium nanoparticles at a level of <100 ppm, administered to the albumin or egg air chamber, did not adversely affect the growth, development and health of birds.…”
Section: The Effect Of Silver On More Developed Organismsmentioning
confidence: 99%
“…Strong inhibitory properties of AgNPs toward herpes simplex virus (HSV) have been reported [ 88 , 103 ]. That report opened the door to the use of AgNPs in the treatment of another viral infections.…”
Section: The Effect Of Silver On More Developed Organismsmentioning
confidence: 99%
“…In comparison, Mitsui-7 MWCNTs induced a statistically significant ( p < 0.05) increase in TNF-α levels 96 h post-exposure ( Figure 4 D). TNF-α levels specifically play a vital role in proinflammatory response assessment because it is expressed in the early stages of cell inflammation [ 65 ]. Therefore, it can be concluded that in a realistic occupational exposure scenario, exposure to MWCNTs does initiate cell inflammation and eventually can result in cell death.…”
Section: Discussionmentioning
confidence: 99%